Pemetaan Jumlah Kasus Speech Delay Di Sekolah Dasar Negeri Inklusif Kota Surakarta: Studi Kasus - Dian Atnantomi Wiliyanto; Rizki Husadani (Journal on Education, 2023)
Delays in children's language and speech development must be immediately recognized by parents, teachers and special assistant teachers at home and at school so that appropriate services can be provided according to needs. This research aims to determine the number and types of cases of delays in language and speech development in regular children and children with special needs who attend inclusive schools in the city of Surakarta. This type of research is qualitative research using a case study design. The subjects of this research were class teachers and accompanying teachers at Inclusive Elementary Schools in Surakarta City with a total of 238 Students with Special Needs (SSN). Data collection techniques used closed questionnaires. Data analysis techniques use statistical tests and use Arc GIS software. The results of this research are mapping of speech delay cases in Surakarta City Inclusion Elementary Schools at SSN showing that the number of cases that occurred was 76 cases of speech delay. The distribution of speech delay cases is found in all inclusive elementary schools in Surakarta City. The highest number of cases of speech delay experienced by SSN was at SDN Nayu Barat II Surakarta with 12 PDBK experiencing speech delay. Cases of speech delay experienced by SSN students at Inclusive Primary Schools were most prevalent among male SSN, totaling 62 students.